2016
DOI: 10.1016/j.ympev.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of two new species of Eleotris (Gobiiformes: Eleotridae) in the western Atlantic

Abstract: Fishes of the genus Eleotris present highly conserved morphology, which may make their recognition difficult. Here, two cryptic Eleotris lineages from five locations along the coast of Brazil were identified using the COI gene and two nuclear fragments. High bootstrap and posteriori values supported those lineages, and the genetic distance of COI varied from 6% between the two lineages to 14.1% from other western Atlantic Eleotris species, such as E. pisonis, E. amblyopsis and E. perniger. The reciprocal monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
8
1
2
Order By: Relevance
“…Based on the K2P distance matrix, the COI identification system may help define the limits of nucleotide divergence used to separate lineages (Hebert et al., ). The pairwise genetic distance matrix (Table ) showed considerable divergence between groups, varying from 5.2% to 25.0%, values that are consistent with divergence estimates in studies that have designated new fish species from comparisons with recognized taxa (Amaral et al., ; Baldwin, Cristina, & Lee, ; Bariche et al., ; Connell, Victor, & Randall, ; Guimarães‐Costa et al., ; Melo, Benine, Mariguela, & Oliveira, ; Oliveira et al., ; Tornabene et al., ; Van Tassell, Joyeux, Macieira, & Tornabene, ; Victor, Hanner, Shivji, Hyde, & Caldow, ). When the 2% species threshold for COI sequences (Hebert et al., ) is applied to the data analyzed in the present study, three of the 14 species sampled, Gobiomorus dormitor , Eleotris fusca and Dormitator maculatus , presented evidence of genetic structuring throughout their distribution in the Neotropical and Indo‐Pacific regions, based on nucleotide divergence values of 5.2%–13.1%, as well as reciprocal monophyly between lineages.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Based on the K2P distance matrix, the COI identification system may help define the limits of nucleotide divergence used to separate lineages (Hebert et al., ). The pairwise genetic distance matrix (Table ) showed considerable divergence between groups, varying from 5.2% to 25.0%, values that are consistent with divergence estimates in studies that have designated new fish species from comparisons with recognized taxa (Amaral et al., ; Baldwin, Cristina, & Lee, ; Bariche et al., ; Connell, Victor, & Randall, ; Guimarães‐Costa et al., ; Melo, Benine, Mariguela, & Oliveira, ; Oliveira et al., ; Tornabene et al., ; Van Tassell, Joyeux, Macieira, & Tornabene, ; Victor, Hanner, Shivji, Hyde, & Caldow, ). When the 2% species threshold for COI sequences (Hebert et al., ) is applied to the data analyzed in the present study, three of the 14 species sampled, Gobiomorus dormitor , Eleotris fusca and Dormitator maculatus , presented evidence of genetic structuring throughout their distribution in the Neotropical and Indo‐Pacific regions, based on nucleotide divergence values of 5.2%–13.1%, as well as reciprocal monophyly between lineages.…”
Section: Discussionsupporting
confidence: 76%
“…The alignment of the whole COI matrix resulted in a sequence of 632 bps, with K2P intraspecific distances ranging from 0% to 11%. The Bayesian and neighbor‐joining analyses of the relationships among species produced similar topologies (Figure ), with 23 highly divergent clades, consisting of the following groups: eight clades corresponding to the valid species Eleotris amblyopsis , E. pisonis , E. picta , Gobiomorus polylepis , Hemieleotris latifasciata , Gobiomorus maculatus , Guavina guavina and Dormitator latifrons ; two new lineages of the Eleotris (North 1 Lineage and Northern 2 Lineage; Guimarães‐Costa et al., ); Eleotris fusca lineage I, E. fusca lineage II and E. fusca lineage III; Gobiomorus dormitor lineage I and G. dormitor lineage II, Dormitator maculatus lineage I, D. maculatus lineage II and D. maculatus lineage III; Microphilypnus lineage I, Microphilypnus lineage II and Microphilypnus ternetzi . The neighbor‐joining tree generated a topology similar to that of the Bayesian analysis, with the principal clades also being supported by high bootstrap values (data not shown).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Van Tassell et al (2015) reported two resident species of Gobiosoma (denominated here as Gobiosoma spp.) endemic to intertidal areas of the Amazon estuary, as we observed in Eleotris (Guimarães-Costa et al, 2016), which has two endemic intertidal resident species (currently undescribed) in the AE and NM subprovinces, one of which (from the NM) was not record in the present study. This high degree of endemism may be accounted for by sympatric speciation events, through which the local drivers (e.g., environmental filters) of a subprovince may promote scenarios favorable to speciation at a local-scale (Doebeli and Dieckmann, 2003;Rocha et al, 2005;Bowen et al, 2013).…”
Section: Biogeographic Patternscontrasting
confidence: 38%
“…One other process that should be considered is ephemeral ecological speciation (Cutter and Gray, 2016;Pinheiro et al, 2017), given the observation of one new Gobiosoma species closely related to Gobiosoma alfiei (Van Tassell et al, 2015), and the other two new, cryptic Eleotris species (Guimarães-Costa et al, 2016), which probably evolved in the context of dynamic changes in the characteristics of the Amazon barrier (run-off, sedimentation rates) over geological time (Joyeux et al, 2001;Rocha, 2003). This incipient speciation would be the result of intermittent dispersal and colonization events (Cutter and Gray, 2016;Pinheiro et al, 2017).…”
Section: Biogeographic Patternsmentioning
confidence: 99%